(3JGQjN GdYdeGA GdfMhjjf ef GdHUQjjf hGdchajjf hZjQges - (3CHh GdeMGSf GdeaVd Hf eMeO Hf eSYQ,J (B443 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf , CMeOg QVi GdMeO dg hCRcGg YfOg Efi CPcQ Pdc eeG OYGfi Edi eG ChOYg ai gPG GdcJGH s
(3BNQgG (B:s
(3CHh YeQh hGdcSGFQ bO PcQJ haGJgeG QMegeG Gddg ai LedI eG PcQJg ai CNHGQ GdfMhjjf , hGdMeO ddg Mb MeOg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B71 - (3U(B89s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ GdYfGhjjf Ydi GdgGeT HGdMeQI s
(3hYdi GdfSNI Jedc HGSe eMeO Hf LGQ Gddg Hf agO GdgGTei s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
Keywords: (3GdJGQjNs